Studi Korelasi antara Pengetahuan Kurikulum Ismubaristik dengan Sikap Sopan dan Santun pada Siswa - Sara Aulia Fathin; Erhamwilda (Jurnal Riset Pendidikan Agama Islam, 2022)
Abstract. Education is learning process so that students actively develop their potential to have religious spiritual strength, self-control, personality, intelligence, noble character and skills needed by themselves, society, nation and state. SD X is one of the schools that seeks to realize an education system that aims to make students have personality, intelligence and noble character and character by the establishment of a local content curriculum called the Ismubaristic Curriculum. The purpose of this study was to determine the extent of students' knowledge of the Ismubaristic Curriculum, students' polite and courteous attitudes and the relationship between the Ismubaristic curriculum and students' politeness and courtesy. The researcher uses correlational analysis method with quantitative approach. The population selected in this study was 188 students. Data collection techniques used are quistionnaires, interviews and observations. The results of this study indicate that: (1) Knowledge of the Ismubaristik Curriculum of Class V SD X has good kowledge, this is evidenced by the average score of the quistionnaire results of 58.89. (2) The polite and courteous attitude of the fifth grade students of SD X is very good with an average quistionnaire score of 70.29. (3) The relationship between knowledge of Ismubaristic Curriculum with polite and courteous attitudes for fifth grade students at SD X is very good with a correlation value of 0.356 or 35.6%. Abstrak. Pendidikan adalah proses pembelajaran agar peserta didik secara aktif mengembangkan potensi dirinya untuk memiliki kekuatan spiritual keagamaan, pengendalian diri, kepribadian, kecerdasan, akhlak mulia serta keterampilan yang diperlukan dirinya, masyarakat, bangsa dan negara. SD X merupakan salah satu sekolah yang berupaya untuk mewujudkan sistem pendidikan yang bertujuan untuk menjadikan peserta didik memiliki kepribadian, kecerdasan dan akhlak mulia serta berkarakter dengan dibentuknya sebuah Kurikulum muatan lokal yang dinamakan Kurikulum Ismubaristik. Tujuan dari penelitian ini adalah untuk mengetahui sejauh mana pengetahuan Kurikulum Ismubaristik siswa, sikap sopan dan santun siswa serta keterkaitan diantara kurikulum Ismubaristik dengan sikap sopan dan santun siswa. Peneliti menggunakan metode teknik analisis korelasional dengan pendekatan kuantitatif. Populasi yang dipilih dalam penelitian ini adalah 188 siswa. Teknik pengumpulan data yang digunakan adalah kuisioner, wawancara dan observasi. Hasil dari penelitian ini menunjukan bahwa: (1) Pengetahuan Kurikulum Ismubaristik siswa Kelas V SD X memiliki pengetahuan yang baik Hal ini dibuktikan dari nilai rata-rata hasil angket sebesar 58.8989. (2) Sikap sopan dan santun siswa Kelas V SD X sangat baik dengan nilai rata-rata angket sebesar 70,2979. (3) Hubungan Antara Pengetahuan Kurikulum Ismubaristik dengan Sikap Sopan dan Santun Siswa Kelas V SD X sangat baik dengan nilai korelasi sebesar 0,356 atau sebesar 35.6 %.